Current Pharmaceutical Design on Adhesive Based Transdermal Drug Delivery Systems - Ghosh, Animesh; Banerjee, Subham; Kaity, Santanu; W. Wong, Tin (Current Pharmaceutical Design, 2015)
Drug-in-adhesive transdermal drug delivery matrix exploits intimate contact of the carrier with stratum corneum, the principal skin barrier to drug transport, to deliver the actives across the skin and into the systemic circulation. The main application challenges of drug-in-adhesive matrix lie in the physicochemical properties of skin varying with age, gender, ethnicity, health and environmental condition of patients. This in turn poses difficulty to design a universal formulation to meet the intended adhesiveness, drug release and drug permeation performances. This review focuses on pressure-sensitive adhesives, and their adhesiveness and drug release/permeation modulation mechanisms as a function of adhesive molecular structure and formulation attributes. It discusses approaches to modulate adhesive tackiness, strength, elasticity, hydrophilicity, molecular suspension capability and swelling capacity, which contribute to the net effect of adhesive on skin bonding, drug release and drug permeation.
Keywords: Drug-in-adhesive